Bulk and surface properties related to composite filler size - Kátia Gerhardt; Andrea Soares Quirino da Silva; Guilherme Rego; Mário Alexandre Coelho Sinhoreti; Vinicius Esteves Salgado; Luis Felipe J. Schneider (Universidade Estadual de Campinas, 2015)
There are few studies that fully characterize the effect of the filler size on the surface, optical and mechanical properties of resin composites. Aim: To determine the influence of the filler size content on surface, optical and mechanical properties before and after accelerated aging. Methods: Seven resin composites were investigated: Filtek Supreme® (3M/ESPE), Estelite Σ Quick® (Tokuyama), Evolu-X® (Dentsply), Esthet-X HD® (Dentsply), Opallis® (FGM), Herculite XRV Ultra® (Kerr) and Filtek Z250® (3M/ESPE). Elastic modulus (EM) and flexural strength (FS) were determined by three-point bending of specimens immersed or not in absolute ethanol for seven days. Roughness (Ra) and gloss (G.U.) analyses were determined before and after ethanol storage for seven days and CIELAB color change (∆E*) was obtained with a spectrophotometer. Results were analyzed by two-way ANOVA (general linear model) for EM and FS, with repeated measures for roughness and gloss, and one-way ANOVA for ∆E*. All comparisons were performed by Tukey's test (5%). Pearsons' correlation test was performed to determine the correlation between EM, FS, roughness, gloss, and ∆E* with the mean filler sizes. Results: Mechanical properties decreased for all materials when submitted to immersion in ethanol. Increasing filler size gradually increased EM, FS and roughness values; gloss values decreased and didn't significantly affects ∆E*. Nanofiller composites presented higher gloss values than the others. Conclusions: It was possible to determine that the average filler size is a good predictor just for FS and gloss retention.